Surface features of strongly heated bulk tungsten divertor plates at ASDEX Upgrade. (March 2023) - Rohde, V.; Balden, M.; Hunger, K.; Zammuto, I.; Herrmann, A.; Neu, R.; ,
Highlights: Horizontal cracks and humps at the surface were observed at ASDEX Upgrade solid tungsten divertor plates. Recrystallization and grain growth is found at these locations. High thermal stress due to temperature gradients is discussed to produce these cracks. He bubble formation in tungsten is discusses as source of the surface humps. Abstract: Solid tungsten tiles exposed at the outer strike point module of the ASDEX Upgrade divertor show cracks parallel to surface in the bulk and humps at the surface. At ASDEX Upgrade these horizontal cracks were observed for the first time. About 10 % of all tiles exhibit protrusions originated by horizontal cracks about 3–5 mm below the surface. The position of this damage coincidence with the location of highest deposited energy, which varies for the different tiles due to the mounting. The tungsten at the locations of the horizontal cracks exhibits recrystallization and grain growth, presumably due to the worse thermal contact caused by the horizontal cracks. Although, the operation of AUG was not hampered by these damages, these tiles had to be exchanged preventing progression of these damages. High thermal stress due to temperature gradients is discussed to originate these cracks. Additionally, humps are found at the surface at the position of high heat flux. Their occurrence seems to be related to the increased number of high power discharges. Focused ion beam prepared cross sections indicate pores and cavities in and below these humps. This finding is discussed in the view of He bubble formation in tungsten.